COGNITIVE MECHANISMS OF PERCEIVING THE “MARVELOUS” IN SPANISH LITERATURE OF FANTASTIC REALISM: A COGNITIVE-STYLISTIC ANALYSIS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the cognitive mechanisms underlying the perception of the “marvelous” in Spanish literature of fantastic realism, with a particular focus on the interplay between cultural cognition, narrative strategies, and stylistic devices that shape readers’ experiences of the fantastic. Drawing on insights from cognitive stylistics, conceptual metaphor theory, and narratology, the study analyzes how Spanish authors situate the marvelous within ordinary contexts, creating a dual perception of reality that blurs the boundaries between the real and the fantastic. The article highlights the role of cognitive frames, schemas, and mental models in guiding interpretation, showing that the marvelous emerges not only from textual structures but also from readers’ culturally embedded cognitive processes. Special attention is given to the works of Gabriel García Márquez, Alejo Carpentier, and contemporary Spanish-language authors, where the marvelous functions as both a literary device and a cultural code. By tracing the mechanisms of defamiliarization, frame blending, and embodied experience, the article argues that fantastic realism engages readers in a continuous cognitive negotiation between belief and disbelief, producing a unique mode of aesthetic perception. The findings demonstrate that the “marvelous” in Spanish fantastic realism cannot be reduced to textual ornamentation; it represents a cognitive-stylistic phenomenon grounded in the interaction of linguistic form, cultural semantics, and mental imagery.